Optimizing the Production of Beef Cattle Utilizing Palm Oil Leaf Sheet Ammoniation Supplemented by Sulfur Minerals, Phosphorus and Cassava Leaf Flour - Suyitman; Warly, Lili; Rachmat, Arif; Ramadhan, Dear Rahmatullah (Pakistan Journal of Nutrition, 2017)
Objective: This study was designed to explore the effects of supplementing processed leaf-based palm leaf rations with minerals [sulfur (S) and phosphorus (P)] and cassava flour on the optimization of bioprocess in the rumen and beef cattle growth performance. Materials and Methods: Simmental beef cattle were divided into 5 treatments and 4 replicates. The treatments consisted of A = Field grass+concentrate (60%: 40%, used as the control), B = Palm frond ammoniation + concentrate (60%: 40%), C = B + mineral supplementation S (0.4%) and P (0.27%), D = B + cassava flour (5%) and E = C + cassava flour (5%). The consumption of dry matter rations, dry matter digestibility, weight gain and feed efficiency was evaluated. Results: it is observed that the treatments had significantly different effects on Simmental cattle growth performance (p